Estimation of Microfinance Demand and Supply: With Special Reference to Assam - Sarma, Gopal Kumar; Borbora, Saundarjya (International Journal of Social Sciences and Management, 2015)
The paper delves to estimate microfinance demand, supply and its mismatch in India in general and Assam in particular. Since exact estimation is a bulky task, it adopts an approximation model based on poverty database, mixmarket database and some complementary reports on microfinance. The study shows that microfinance demand has shown a trend of increasing growth for India as well as Assam and stands its candidature as a potential matured market in future. The supply of microfinance for India as a whole is at low level, which shares only 0.70 per cent of gross domestic product of India. From the regional perspective, southern region dominates the supply of microfinance and Assam shares the least. The study indicates a huge mismatch between demand for and supply of microfinance and considering mixmarket average loan size all the regions of India are deficient in terms microfinance supply. The study further indicates some of the possible reasons for the mismatch.  Int. J. Soc. Sci. Manage. Vol-2, issue-4: 308-314